Polarimetric imaging for air accident investigation - Privett, G. J.; Ashe, M. D.; Greaves, Matthew J.; Holland, D.; Davidson, L. (SPIE - International Society for Optics and Photonics, 2012)
We report a trial wherein a simple 4 CCD visible-band Polarimetric Imaging (PI) camera was fielded against aircraft debris distributed across an arid terrain, a littoral region and a small number of maritime debris targets A debris field realistically simulating an aircrash and a debris grid of aircraft remains were observed from an air platform flying in dry and sunny conditions. We report PI utility in support of air accident investigation by an enhanced ability to successfully locate small targets within the scene via the use of colour enhanced and decorrelated intensity PI products. Our results indicate that handheld PI capability may represent an effective low cost, upgrade and augmentation option for existing and future imaging systems that would support air accident investigators and assist in the cueing of more sophisticated assets and/or analyst attention.
Keywords: Polarimetric imaging; passive; visible band; air accident investigation